Ha(e)ndlowe pasaże. Reklama kultury versus kultura w reklamie - Okupnik, Małgorzata (Poznańskie Spotkania Językoznawcze, 2015)
In the essay “Ha(e)ndels passages” the slogans of the Poznań Philharmonic were analyzed. The research had two aims. The first goal was to verify whether the advertisings texts, inducing people to the participation in musical events, really differ from the typical commercial advertising. The second aim consisted in the examination if the language of the slogan determines its autonomy and peculiarity. The review of slogans proved that their authors use various communication and language games. Slogans of the Poznań Philharmonic are inventive and intriguing. Cultural organizations are obliged to pay attention to the language of advertisings texts. In promotional campaigns they must not go beyond standards and descend into the level of pop culture.